Addressing vaccine hesitancy: the LEARN approach - Taneja, Gunjan (International Journal Of Community Medicine And Public Health, 2022)
Immunization programs today stand at crossroads. Even as COVID vaccine campaigns continue, inequity, concerns and confusion around them seems ever expanding. While vaccine hesitancy in some form or the other has existed since the inception of vaccination, the complex and dynamic world that we live in now has resulted in hesitancy to vaccines become an outcome of myriad interactions that we encounter in our day to day lives. Factors extraneous to health systems are major determinants and it is essentially the culmination of economics, politics, science, and technology impacting human behaviors and emotions which result in a parent, family or a community arrive at the decision of whether to or not to vaccinate. Vaccine hesitancy is on the rise, it is becoming more organized and now is not just a problem of high- income countries. It is imperative that as public health advocates, academicians, policy makers, managers and implementers we recognize it and adopt a non-judgmental and non-partisan approach built on empathy, respect and trust and not just scientific knowledge and theorems to address it. The current paper puts forward a novel approach to address hesitancy, the LEARN approach: and advocates that we need to ‘Listen’ to the voices of concern, ‘Engage’ with all stakeholders, ‘Articulate’ and communicate better in a language which is simple and comprehensible, ‘Reflect’ on what works and what does not and at the same time ‘Negate’ events and episodes which dent confidence in science and promote complacency.